Efficiency of invertebrate-based bioassessment for evaluating the ecological status of streams along a gradient of flow intermittence. (December 2021) - Crabot, Julie; Dolédec, Sylvain; Forcellini, Maxence; Datry, Thibault
Highlights: Most metrics decreased linearly with increasing flow intermittence. Detection efficiency of contamination by sewage was lower at intermittent reaches. No functional traits responded to contamination by sewage. Abstract: Intermittent rivers and ephemeral streams (IRES) represent the majority of the global river network, support high biodiversity and provide multiple ecosystem services. However, they are being degraded at alarming rates, and it may be questioned whether current invertebrate-based biomonitoring protocols, which were designed for rivers and streams that flow all year round, are also appropriate for assessing the ecological status of IRES. Here, we test for the first time the efficiency of the French invertebrate-based biomonitoring indicators to assess the ecological status of intermittent rivers downstream six sewage treatment plants along a gradient of flow intermittence (i.e., the percentage of a year without flow at a given site). We found that the effects of drying confounded with that of sewage and in most cases, current biomonitoring metrics did not distinguish between the effect of sewage and those of drying. Except for the taxonomic richness of invertebrates resistant to drying, all metrics decreased linearly with increasing flow intermittence. In addition, the efficiency for detecting sewage effects was lower at intermittent reaches compared to perennial reaches. Last, we identified biological traits responding to flow intermittence, but not to sewage effluents, and we further discuss the implication for traits-based monitoring. If current biomonitoring protocols calibrated for perennial rivers could still be applied to reaches prone to weak flow intermittence, alternatives are urgently needed for integrating intermittent rivers into current biomonitoring national programs.